Vascular epiphytes in seasonal semideciduous forest in the State of Espírito Santo and the similarity with other seasonal forests in Eastern Brazil - Dayvid Rodrigues Couto; André Paviotti Fontana; Ludovic Jean Charles Kollmann; Vitor da Cunha Manhães; Talitha Mayumi Francisco; Gláucio de Mello Cunha (Acta Scientiarum. Biological Sciences, 2016)
In this study, we evaluated the floristic composition of vascular epiphytes in seasonal semideciduous forest fragments of the Itapemirim River basin, Southern State of Espírito Santo, in order to verify its similarity to other semideciduous forests studied in Brazil. Excursions were conducted every fortnight between June 2008 and May 2009, and epiphytes were collected and recorded (55 species, 34 genera and six families). Orchidaceae (21 species) was the richest family, whereas the genera presenting the greatest richness were Tillandsia (seven), Rhipsalis (four), Aechmea, Epidendrum and Peperomia (three species each). The category the most representative was characteristics holoepiphytes (84%). The riparian forests were the most important environments for the epiphytic flora. Similarity analysis and PCA supported four groups, where the study area appears disjointed from the others, supporting the hypothesis that geographical proximity, elevation and climate have a strong effect on the floristic composition, conditioning the formation of distinct floras. Detailed surveys on the floristic composition and structure of this community are important for the elaboration of studies on coherent environmental impacts, since epiphytes are typical in tropical rainforests, and they are an important floristic, structural and functional component of these ecosystems.